2020
DOI: 10.1111/jocn.15485
|View full text |Cite
|
Sign up to set email alerts
|

Older people’s early experience of household isolation and social distancing during COVID‐19

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
74
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(85 citation statements)
references
References 39 publications
5
74
0
1
Order By: Relevance
“…This was considered the only way to interact in a ‘corona friendly’ way. The patients experienced that to some degree using social media could ease feelings of deprivation and anxiety, which also be seen in other studies (Brooke & Clark, 2020; Brooks et al, 2020; Xu et al, 2020).…”
Section: Discussionsupporting
confidence: 79%
“…This was considered the only way to interact in a ‘corona friendly’ way. The patients experienced that to some degree using social media could ease feelings of deprivation and anxiety, which also be seen in other studies (Brooke & Clark, 2020; Brooks et al, 2020; Xu et al, 2020).…”
Section: Discussionsupporting
confidence: 79%
“…One study reported a higher usage of electronic products by older people [149], whereas others reported contrasting findings [74,81]. Participants felt blessed, lucky, and fortunate to be able to stay in contact with others through social media [91]. Variation in game use by older adults did not differ from that observed in younger populations [167].…”
Section: Life Habitsmentioning
confidence: 91%
“…Despite the problems with perceiving older adults as a homogeneous risk group and the potential isolation of older people who are not digitally savvy, solidarity between the generations and among neighbors has generally been strengthened by the current crisis (Brooke and Clark, 2020; Jones et al, 2020). Creative solutions have emerged, such as telephone networking to do shopping for older neighbors.…”
Section: Current Discussion Within Gerontological Social Workmentioning
confidence: 99%